Typologies of Intimate Partner Violence Against Women in Five Latin-American Countries: A Latent Class Analysis (2022)
ABSTRACT: Objectives: To estimate typologies of Intimate Partner Violence against women in some Latin-American countries. Methods: Multistage sampling survey included women aged 15 to 49 (n = 63,321). Latent class analysis was estimated, including psychological, physical, and sexual violence and control. Results: The three-class model had a better fit. 1) The high-level IPV class (23%) comprised those suffering high levels of violence. They had higher education and wealth index, lived in urban settings, and their husbands used alcohol more. 2) The middle-level IPV class (45%) suffered high levels of control but low levels of other violence. They justified IPV more than other classes and this group had a high proportion of women without education. 3) Women in the non-IPV class (32%) did not report IPV. Conclusion: Three typologies of IPV were found: high-level, middle-level, and non-IPV. Policies should create screening, early prevention strategies, and programs based on these typologies. The high-level IPV group can benefit from intense legal and mental health interventions, including alcohol reduction and women's empowerment. The middle-level IPV group could benefit from interventions to reduce violence justification and increase women's education.